Ornamental Fish Marketing at Laladon Ornamental Fish Exchange, Bogor, West Java - Daffa Nuradzani; Yani Hadiroseyani; Irzal Effendi; Tatag Budiardi (CV. Syntax Corporation Indonesia, 2024)
The ornamental fish business in Indonesia, especially at Laladon Ornamental Fish Exchange, Bogor, has experienced a significant decline after the Covid-19 pandemic. This study aims to analyze the factors that influence the sale of ornamental fish at the location. The research was conducted from May to August 2023 using purposive sampling method on 9 active ornamental fish traders. Data collected included location profile, technical and economic aspects of marketing. Data analysis was carried out with qualitative and quantitative descriptive analysis, as well as statistical tests using Kruskal-Wallis and Spearman rank correlation. The results showed that the variables that significantly influenced sales were fish stock (0.833), number of fish species (0.711), fish storage capacity (0.833), repeat purchases by businesses (0.900), and fish sales (0.983). The decline in sales in the post-pandemic period was caused by various internal and external factors. These findings indicate the need for improvements in product management and marketing strategies to improve sales performance of ornamental fish at Laladon Ornamental Fish Exchange. This research provides important insights for businesses and stakeholders in optimizing the potential of the ornamental fish market.